The impact of ethical leadership on employee creative deviance: the mediating role of job autonomy. Issue 2 (23rd December 2020) - Liu, Xiaoqin; Baranchenko, Yevhen; An, Fansuo; Lin, Zhibin; Ma, Jie
Abstract : Purpose: This study aims to explore the impact of ethical leadership on employee creative deviance, with job autonomy as a mediator and creative self-efficacy as a moderator between job autonomy and creative deviance. Design/methodology/approach: A survey was developed based on construct measures from the literature. A total of 316 responses were received from employees of information and communication technology companies located in China's Pearl River Delta. Findings: Both ethical leadership and job autonomy have a positive impact on employee creative deviance; job autonomy plays a mediating role between ethical leadership and creative deviance; creative self-efficacy does not have a significant moderating effect on the job autonomy-creative deviance relationship. Research limitations/implications: Future studies could explore the potential moderating role of both job autonomy and creative-self efficacy in the link between ethical leadership and creative deviance. Practical implications: This study recommends that organizations should adopt and promote an ethical leadership approach to manage creative deviance at work. Organizations could explore alternative methods of task completion to support the job autonomy for the employees to mitigate the dilemmas associated with creative deviance. Originality/value: This is one of few studies that examine the impact of ethical leadership on employee's creative deviance, despite the fact that the influence of ethical leadership on the followers has been extensively examined.